Studi Tingkat Tutupan Terumbu Karang di Kawasan Konservasi Perairan (KKP) Pulau Mare Kota Tidore Kepulauan - Mahruf Azis; Nurain Adung Damsiki; Ainuddin Ainuddin (Jurnal Ilmiah Wahana Pendidikan, 2022)
The Marine Conservation Area (MPA) of Mare Island has various potentials from the ecological, socio-cultural to economic aspects with important benefits. The ecological potential of coral reef ecosystems in the Marine Protected Area of ​​Mare Island has an area of ​​146.19 ha. The Mare Island Marine Protected Area supports people's lives, especially those who live in coastal areas. This study aims to determine the condition of coral reefs, as the basis for making policies on the management of coral reef ecosystems in the Marine Protected Area of ​​Mare Island. Coral data was collected using the line transect method or LIT (Line Intercept Transec). The coral cover measurement data was then calculated the percentage cover to determine the percentage of coral reef cover at the study site. The results of the calculation of the percentage cover (percent cover) are then determined the category of coral reef conditions based on the standard criteria for damage to coral reefs based on the Decree of the Minister of the Environment No. 4 of 2001 as follows: two locations are in good category, namely Goma observation location (63.2%) and Taisa (49%), while the observation locations Tahula (45.1%), Bagyan (33.4%), Kofo Masako (31.2%) and Akebai (36.3%) were in the medium category